List apostolski Benedykta XVI z okazji 1600. rocznicy śmierci św. Jana Chryzostoma - XVI, Benedykt (Vox Patrum, 2009)
Apostolic Letter of Benedict XVI on the Occasion of the 1600th Anniversary of the Death of St. John Chrysostom